PERUBAHAN SOSIAL BUDAYA MASYARAKAT PEDESAAN PASCA REVOLUSI HIJAU - Adam Saleh (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2021)
It is assumed that changes in village community will become even clearer if related to changes in village society at this time. Changes in society will look good in the fields of education, economics, social relations and other fields. Modernization is a change in society that moves from traditional conditions or from pre-modern society to modern society. The process of change was driven by various community efforts in fighting for their hopes and ideals, namely changing lives and existing livelihoods for the better. General characteristics of modernization are related to the fields of social social traditions, population science and technology and social mobility. The various fields are proceeding so as to achieve new patterns of behavior that are manifested in the life of modern society. Major changes that have taken place since the post-green revolution, villages in Southeast Asia have undergone fundamental changes. Rural life and the fulfillment of the needs of life of rural people in Southeast Asia have undergone a fundamental change, can no longer assume that the fulfillment of rural life needs are obtained from agriculture, nor can it assume that rural people face and expect their future in the field agriculture, these events affect each other or the interconnection between rural and urban areas, such as increased movement of rural people to cities or vice versa (urbanization and migration), the shift from agriculture to non-agriculture (agrarian-industrial transformation), as well as increased aspirations and education (social mobility Another thing that seems to change is lifestyle in the form of material, in this case related to household appliances, vehicles and communication tools.